Hepatoid Adenocarcinoma of Stomach: Emphasis on the Clinical Relationship with Alpha-Fetoprotein-Positive Gastric Cancer. (13th December 2019) - Chen, Er-Bao; Wei, Yi-Chou; Liu, Hai-Ning; Tang, Cheng; Liu, Meng-Ling; Peng, Ke; Liu, Tianshu
Abstract : Aims . Both hepatoid adenocarcinoma of stomach (HAS) and alpha-fetoprotein-positive gastric cancer (AFPGC) are rare but aggressive subtypes of gastric cancer, but few studies focus on the clinicopathologic differences and prognostic factors between them because of their rarity and histologic overlap. And the significance of AFP level in HAS prognosis was not well studied. Methods . 41 patients with AFPGC and 52 patients with HAS were included in this study. The clinicopathologic features were compared by Chi-square analysis. Prognostic factors for overall survival (OS) and disease-free survival (DFS) were analyzed with the Kaplan-Meier method. Results . The patients with HAS were of a younger age compared with AFPGC, and nearly 60% of tumor located in the gastric antrum and the gastric fundus of cardia. The OS of AFPGC was shorter than that of HAS, due to a higher rate of metastasis. Furthermore, the survival analysis showed that HAS with high AFP expression (AFP High HAS) had a significantly poorer OS compared to HAS with low AFP expression (AFP Low HAS) (P = 0.046 ). Conclusions . Compared with AFPGC, the patients of HAS were of a younger age and had less rate of liver and other organ metastasis. The serum AFP level was a sensitive prognostic indicator for OS. Therefore, much attention should be paid to AFP High HAS in clinical practice.